OPTIMIZATION OF TUNED MASS DAMPERS ATTACHED TO DAMPED STRUCTURES - MINIMIZATION OF MAXIMUM DISPLACEMENT AND ACCELERATION - Jan Štěpánek; Jiří Máca (Acta Polytechnica CTU Proceedings)
A tuned mass damper is a device, which can be highly helpful while dealing with dynamic behaviour of structures. Its proper design is conditioned by knowledge of both loading and the structure properties. In many cases, the structure can be represented by single degree of freedom model, which simplifies the design and optimization of tuned mass dampers. Most of studies focus only on minimization of displacement of the main structure under harmonic force load, however, in many cases, different frequency response function would be more appropriate. This paper presents an extension of design formulas for the H∞ optimization of tuned mass dampers for damped structures and various frequency response functions.